The Role of Mast Cells in the Pathogenesis of Covid-19 - Andrey Valerievich Budnevsky, Evgeniy Sergeevich Ovsyannikov, Roman Evgenyevich Tokmachev, Inessa Alekseevna Savushkina, Nadezhda Gennadievna Alekseeva, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: The Coronavirus Disease 2019 (COVID-19) caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) was first reported in December 2019 in Wuhan. The problem of COVID-19 treatment is still relevant, and it is necessary to study in details the pathogenesis of COVID-19, including the role of mast cells (MCs). Aim: The aim of the review is to reveal the role of MCs, their receptors and mediators in the pathogenesis of the COVID-19. Results: This review demonstrates a possible role of MCs in the pathogenesis of COVID-19. Conclusion: MCs may be key elements of inflammation caused by COVID-19. MCs express various receptors on their surface that ensure the interaction of SARS-CoV-2 and MCs. Activated MCs release inflammatory cytokines, chemokines and proteases, which are involved in both the protective function and hyperinflammation in COVID-19.